Pseudocyst of the auricle-a new method of treatment - Ramalingam, Ravi (Springer India, 1998)
Pseudocyst of the auricle is a rare condition and is hardly encountered in routine ENT practice. There have been only about 200 of these cases reported in world literature. The etiology remains obscure and the treatment modalities uncertain. The authors present their series of 15 cases and review the available literature on this condition. A new and completely successful method of treatment is also presented.